Peran Administrasi Sarana dan Prasarana dalam Pengembangan Lembaga Pendidikan Islam - Fatimah, Meti; Haerullah, Haerullah (Lembaga Yasin AlSys, 2024)
Infrastructure management is a crucial element in the development of Islamic educational institutions; however, its management often faces challenges such as budget constraints and unequal distribution of facilities. This study aims to analyze the role of infrastructure administration in enhancing the quality of education in Islamic educational institutions and how effective management can contribute to the development of these institutions. The research method used is a literature review with a qualitative approach, analyzing various literatures related to infrastructure administration and its implementation in Islamic educational institutions. Data was collected through reviewing relevant journals, articles, and books, and analyzed descriptively. The findings show that effective infrastructure administration, which includes planning, procurement, maintenance, and disposal, plays a significant role in improving education quality. Adequate infrastructure can create a conducive learning environment, improve access to education, and support extracurricular and religious activities. In conclusion, proper management of infrastructure is a key factor in the development of Islamic educational institutions, although challenges such as budget limitations and human resources still need to be addressed for optimal results.